The dynamic simulation model of apples contact interaction - R. Rogatynskyi; R. Hevko; Y. Nykerui; O. Dmytriv; R. Rozum (Қарағанды университетінің хабаршысы. Математика сериясы, 2019)
The mathematical model of apples shock interaction with each other and with working surfaces of technological equipment during their gathering, transportation and technological processing has been presented. In the model using the Hertz theory, strain and other running parameters of bodies shock interaction have been determined. To set changes to these parameters in time has been a peculiarity of the model, which allows simulate the process in the mode of the calculated experiment. The graphic change dependences of time contact forces, as well as examples of apples kinematics changes at initial angular and tangential velocities have been given.